C58 on Au(111): a scanning tunneling microscopy study - Bajales Luna, Noelia (2013)
C58 fullerenes were adsorbed onto room temperature Au(111) surface by low-energy (∼6 eV) cluster ion beam deposition under ultrahigh vacuum conditions. The topographic and electronic properties of the deposits were monitored by means of scanning tunnelling microscopy (STM at 4.2 K). Topographic images reveal that at low coverages fullerene cages are pinned by point dislocation defects on the herringbone reconstructed gold terraces (as well as by step edges). At intermediate coverages, pinned monomers act as nucleation centres for the formation of oligomeric C58 chains and 2D islands. At the largest coverages studied, the surface becomes covered by 3D interlinked C58 cages. STM topographic images of pinned single adsorbates are essentially featureless. The corresponding local densities of states are consistent with strong cage-substrate interactions. Topographic images of [C58]n oligomers show a stripe-like intensity pattern oriented perpendicular to the axis connecting the cage centers. This striped pattern becomes even more pronounced in maps of the local density of states. As supported by density functional theory, DFT calculations, and also by analogous STM images previously obtained for C60 polymers [M. Nakaya, Y. Kuwahara, M. Aono, and T. Nakayama, J. Nanosci. Nanotechnol. 11, 2829 (2011)], we conclude that these striped orbital patterns are a fingerprint of covalent intercage bonds. For thick C58 films we have derived a bandgap of 1.2 eV from scanning tunnelling spectroscopy data confirming that the outermost C58 layer behaves as a wide band semiconductor.